Association of LDLR, TP53 and MMP9 gene polymorphisms with atherosclerosis in a Malaysian study population - Ahmad, Zalinah; Blin, Joan; Rampal, Lekhraj; Adnan, Rohayu Shahar; Mohtarrudin, Norhafizah; Abang Yusuf, Dayang Sarah Yasmine (Elsevier, 2023)
Preliminary research has shown that low density lipoprotein receptor (LDLR), tumor protein (TP53) and matrix metalloproteinase 9 (MMP9) genes expression levels were significantly increased in atherosclerosis coronary artery tissue (ACAT) compared to non-atherosclerotic coronary artery tissue (NCAT) samples. Thus, further investigation was carried out to study the association of LDLR, TP53 and MMP9 gene polymorphisms and the risk of developing atherosclerosis (ATH) in a Malaysian population. Single nucleotide polymorphisms of C88S, TP53 codon 72 and MMP9C>T were analyzed in 76 ACAT samples and 149 NCAT samples, representing cases and controls, respectively. In results, heterozygous CT genotype of MMP9C>T polymorphism was significantly higher in ACAT compared to NCAT samples (57.9 vs 27.5, ‡2 = 19.758, df= 1, P < 0.05). The CT genotype was found to be significantly associated with the risk of developing ATH (OR = 3.622, 95 CI = 2.028-6.470). However, the distribution of the CT genotype in a healthy Malaysian study population was incomparable regardless of gender and ethnicity. The DNA sequencing results validated the C88S, TP53 codon 72, and MMP9C>T polymorphisms. In conclusion, the CT genotype of the MMP9-1562C>T polymorphism was found to have a strong association with the risk of developing ATH.